Development of advertising strategies to manage the commercialization of post-COVID-19 commercial activity - Lemoine Quintero, Frank Angel (2022)
The present investigation was developed in order to develop advertising strategies that allow managing the commercialization of commercial premises by COVID-19. The study of the state of the art allowed the development of solid criteria for understanding the object-study problem. Subsequently, the service of the business was diagnosed, for which an interview was applied to the owner about the advertising management they carry out and their level of effectiveness reflected in sales, where the Pareto method consisted of the classification by levels of rotation of the products in A, B and C, to define effective advertising strategies. An observation sheet was carried out in the business and a survey was carried out on a sample of 70 clients, evaluating the perception of the effectiveness of the advertising strategies, whose results were processed in the SPSS Software version 21, where the reliability (0.98) is considered very good. Finally, a strategic advertising plan was proposed that includes an analysis at this same level, and the definition of advertising strategies based on the brand, the content and the means of dissemination. It is concluded that the results presented indicate that the strategic plan based on advertising will generate better levels of management, marketing and business positioning.